Effects Of Rejuvenating and Regular Pruning Methods and Levels on Growth, Productivity and Crop Quality in Apple Trees in the SoilClimatic Conditions of the Bukhara Oasis - Djabbarov Bakhtiyor Iskandarovich; Yunusov Rustam; Amonov Abdulaziz Uktamovich (Genius Journals, 2023)
This article provides information about the effect of cutting on the upper part of the tree trunk is directly related to its level and method of cutting, variety characteristics, soilclimatic conditions and resource-saving maintenance levels. In trees that have lost the ability to grow, along with periodic yielding phenomena characteristic of them, there is a decrease in winter resistance compared to normal productive years.
Keywords: agricultural sector; productivity; saline soil